The effect of coffee bean varieties on the hedonic quality of endemic coffee from Banyuwangi - Christina Yunita; Gilang Sandhubaya; Rulli Krisnanda (Jurnal Pariwisata Tourista, 2025)
The development of the beverage industry has driven the growth of local coffee products, including Banyuwangi's endemic coffee, which stands out for its unique flavor characteristics based on its bean varieties. This study aims to determine the preference level for three coffee bean varieties Liberica, Arabica, and Robusta using a hedonic test based on sensory attributes such as acidity, sweetness, bitterness, aroma, and overall liking. The research problem lies in the influence of each coffee bean variety on the sensory perception experienced by respondents through manual brew V60 extraction methods. The research employed an experimental method involving 50 panelists with varying qualifications (untrained, trained, and certified). Data were collected using a hedonic sensory evaluation form with a 5-point scale and analyzed using validity and reliability tests, analysis of variance (ANOVA), mean analysis, and Tukey’s test method through the Minitab application. The results showed that Liberica coffee was superior in terms of acidity, sweetness, and aroma, all of which were favored by the panelists. Robusta coffee received the highest ratings in overall preference, bitterness, and aroma. Arabica coffee received moderate ratings without significant differences compared to the other two varieties. The ANOVA test revealed significant differences in acidity and bitterness attributes (p < 0.05), while aroma and overall liking did not show significant differences (p > 0.05). The Tukey test indicated that the most significant difference was found between the Liberica and Robusta coffee bean varieties. It can be concluded that coffee bean variety significantly affects the sensory evaluation results, with Liberica excelling in acidity, sweetness, and aroma, while Robusta is most preferred overall. These findings contribute to the development of local coffee serving methods and marketing strategies based on coffee bean variety. Keywords: Arabica, Robusta, Coffee Bean Varieties, Hedonic test, Liberica, Sensory evalution